2013
DOI: 10.1021/ic400910g
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth of New Hexahydroxometallates Using a Hydroflux

Abstract: A series of seven compounds, Sr2Mn(OH)6, Ba2Mn(OH)6, Sr2Co(OH)6, Ba2Co(OH)6, Sr2Ni(OH)6, Ba2Ni(OH)6, and Ba2Cu(OH)6, were synthesized using a low-melting hydroflux, a hybrid approach between aqueous hydrothermal and molten hydroxide flux techniques. Crystals of the hexahydroxometallates were obtained by dissolving appropriate amounts of alkaline-earth nitrates or hydroxides and transition-metal oxides, acetates, or chlorides in the hydroflux and reacting at 180-230 °C. The isostructural compounds all crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 61 publications
0
43
0
1
Order By: Relevance
“…Red crystals of K 2− x Fe 4 O 7− x (OH) x (yield >99 %) were obtained by reacting iron(III) nitrate nonahydrate with a mixture of potassium hydroxide and water (molar ratio n (H 2 O) : n (KOH)=1.2) in a PTFE‐lined stainless steel autoclave. Due to the highly corrosive medium, the required constant base concentration and the moderate reaction temperatures, the use of a PTFE‐lined autoclave was deemed prudent, although almost no pressure was generated during the reaction . A screening of the synthesis parameters showed that the reaction is complete even at 100 °C, but yields in small crystallites with sizes below 50 μm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Red crystals of K 2− x Fe 4 O 7− x (OH) x (yield >99 %) were obtained by reacting iron(III) nitrate nonahydrate with a mixture of potassium hydroxide and water (molar ratio n (H 2 O) : n (KOH)=1.2) in a PTFE‐lined stainless steel autoclave. Due to the highly corrosive medium, the required constant base concentration and the moderate reaction temperatures, the use of a PTFE‐lined autoclave was deemed prudent, although almost no pressure was generated during the reaction . A screening of the synthesis parameters showed that the reaction is complete even at 100 °C, but yields in small crystallites with sizes below 50 μm.…”
Section: Resultsmentioning
confidence: 99%
“…Iron oxides and oxoferrates are used in manifold ways, e. g. hexaferrites like BaFe 12 O 19 as magnetic storage materials, [1] BaFeO 2.5 as ion conductor in oxidic high-temperature fuel cells, [2] or hematite Fe 2 O 3 in solar cell technology. [3,4] Beside these examples, there is a variety of other applications for oxidic iron compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Flux crystal growth is an important approach to grow single crystals of new materials212223242526. For exploratory crystal growth of new iridates, KOH and K 2 CO 3 fluxes have typically been used2728.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Thenew all-iron zeolite (ferrolite) was crystallized in ah ydroflux reaction, where Fe(NO 3 ) 3 ·9 H 2 O( 4.28 mmol), Ba(OH) 2 ·8 H 2 O( 4.28 mmol), NaOH (9 g), and H 2 O(7g)were heated at 230 8 8CinaPTFElined stainless-steel autoclave for 24 hours followed by slow cooling at ar ate of 0.3 8 8Cmin À1 to 80 8 8C. [9][10][11] Thenew all-iron zeolite (ferrolite) was crystallized in ah ydroflux reaction, where Fe(NO 3 ) 3 ·9 H 2 O( 4.28 mmol), Ba(OH) 2 ·8 H 2 O( 4.28 mmol), NaOH (9 g), and H 2 O(7g)were heated at 230 8 8CinaPTFElined stainless-steel autoclave for 24 hours followed by slow cooling at ar ate of 0.3 8 8Cmin À1 to 80 8 8C.…”
mentioning
confidence: 99%
“…Thes ynthesis of this new material was enabled by our development of the hydroflux crystal growth technique,which occupies an iche area between hydrothermal synthesis and molten flux chemistry. [9][10][11] Thenew all-iron zeolite (ferrolite) was crystallized in ah ydroflux reaction, where Fe(NO 3 ) 3 ·9 H 2 O( 4.28 mmol), Ba(OH) 2 ·8 H 2 O( 4.28 mmol), NaOH (9 g), and H 2 O(7g)were heated at 230 8 8CinaPTFElined stainless-steel autoclave for 24 hours followed by slow cooling at ar ate of 0.3 8 8Cmin À1 to 80 8 8C. Block crystals measuring 0.05 to 0.1 mm in size with truncated corners were isolated in nearly quantitative yield by removing the residual flux with methanol under sonication.…”
mentioning
confidence: 99%